2020
DOI: 10.1126/sciadv.abc2695
|View full text |Cite
|
Sign up to set email alerts
|

On the crucial role of atmospheric rivers in the two major Weddell Polynya events in 1973 and 2017 in Antarctica

Abstract: This study reports the occurrence of intense atmospheric rivers (ARs) during the two large Weddell Polynya events in November 1973 and September 2017 and investigates their role in the opening events via their enhancement of sea ice melt. Few days before the polynya openings, persistent ARs maintained a sustained positive total energy flux at the surface, resulting in sea ice thinning and a decline in sea ice concentration in the Maud Rise region. The ARs were associated with anomalously high amounts of total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
76
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(85 citation statements)
references
References 54 publications
8
76
1
Order By: Relevance
“…The variability of the polar jet front in the Southern Hemisphere and whether behavior similar to the polar jet in the Northern Hemisphere is underway around Antarctica need to be investigated in future work. Several studies have shown evidence for a wavier jet stream in response to rapid Arctic warming and reported a weakening of the polar jet as a result of a reduced temperature gradient between high and mid latitudes due to the increased temperatures in the Arctic (e.g., Francis and Vavrus, 2015;Coumou et al, 2015;Mann et al, 2017). Such a change in the polar jet, which acts as an isolation boundary between high and mid latitudes, would lead to more interactions and spark feedback mechanisms between the Antarctic system and mid latitudes as happened to be the case in the Arctic (Francis et al, 2018(Francis et al, , 2019b.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The variability of the polar jet front in the Southern Hemisphere and whether behavior similar to the polar jet in the Northern Hemisphere is underway around Antarctica need to be investigated in future work. Several studies have shown evidence for a wavier jet stream in response to rapid Arctic warming and reported a weakening of the polar jet as a result of a reduced temperature gradient between high and mid latitudes due to the increased temperatures in the Arctic (e.g., Francis and Vavrus, 2015;Coumou et al, 2015;Mann et al, 2017). Such a change in the polar jet, which acts as an isolation boundary between high and mid latitudes, would lead to more interactions and spark feedback mechanisms between the Antarctic system and mid latitudes as happened to be the case in the Arctic (Francis et al, 2018(Francis et al, , 2019b.…”
Section: Discussionmentioning
confidence: 99%
“…3a). The moisture and heat carried by the atmospheric river over the ice sheet may have caused warming at the surface due to con- densation (released heat) as well as an increase in downward longwave radiation (e.g., Francis et al, 2020).…”
Section: Explosive Twin Cyclones During 18-22 September 2019 -Preconditioningmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have related these negative ice extent anomalies to various atmospheric and oceanic processes, often related to large, negative anomalies of the Southern Annual Mode (SAM), corresponding increases of cyclonic activity, and warm anomalies of several degrees Celsius at the Antarctic Peninsula and over the Weddell Sea (e.g., Francis et al, 2020;Schlosser et al, 2018;Turner et al, 2020;Wang et al, 2019). Together, these studies concluded that these processes contributed to warmer air, increased cloud-radiation feedbacks, increased liquid precipitation, and increased turbulent heat fluxes into the ice (e.g., Francis et al, 2020). In addition, earlier seasonal sea ice retreat, anomalous surface winds, and strong atmosphere-ocean coupling caused stronger heat absorption by the upper ocean, more southward Ekman transport of warmer surface waters, and thus the warming of the Ocean Mixed Layer, amplifying the sea-ice loss (Meehl et al, 2019;Turner et al, 2020).…”
Section: A Below)mentioning
confidence: 99%